The investigation of clinical and radiological findings of hepatic alveolar cyst hydatid disease (Annals of Medical Research, 2021)
None
Keywords: Echinococcosis Multilocularis; Liver; Multislice Computed Tomography; Magnetic Resonance Imaging.